Os múltiplos cenários futuros da Fábrica Santa Amélia no contexto turístico de São Luís/MA - LEITE, Brenda Rodrigues Coelho (2018)
Recognized for its beautiful buildings, the Historical Center of São Luís, Humanity Heritage, has become the main cultural and touristic attraction of the Capital. Despite the title conferred on it, it is possible to verify in a brief walk through the area that the buildings are in an endless process of revitalization, with deadlines expired and without any new utility. Within this reality, became of concern the future of the heritage of Santa Amélia, an important factory of Maranhão’s industrial period of the late nineteenth century, and of unique Portuguese architecture, chosen to host the courses of Tourism and Hospitality of the Federal University of Maranhão. The concern with this heritage occurs around its recovery from degradation through its restoration and requalification, which has lasted almost 10 years since the beginning of its project, which is still in its final stages, even after its inauguration in 2015, which has generated different expectations, opinions and uncertainties about its future, mainly by students and the local community. Therefore, the construction of the multiple scenarios of Santa Amélia’s factory future for the year 2027 is sought through the Delphi method and consultations with specialists who have a well-known knowledge of the factory and its region. It is investigated not only as a teaching space, as proposed in its project, but also as a possible tourist attraction, as being feasible according to works by Barreto (2007), Kuhl (2006), Choay (2001), among others, authors that compose the theoretical research of this research. For the elaboration of the scenarios, a collection of factors of future and their interrelationships were carried out, which are capable of directing the construction of what is to come. As a result, three alternative scenarios were constructed, the first in a possible future context, the second in an optimistic scenario compared to the possible, and the third in a pessimistic scenario.The scenarios were also able to show the weaknesses and future difficulties that the factory may experience as it develops its activities as the future factors present themselves. Faced with the built-up scenarios, this dissertation becomes a tool to sensitize social actors to a decision making that directs the construction of the best scenario for Santa Amélia.